Incidence and Risk Factors of Chemotherapy-Induced Hepatotoxicity: A Cross-Sectional Study - Sebisaalu Joel; Sarad Pawar Naik Bukke; Bharath Kumar Mamilla Mugaiahgari; Julius Kyomya; Kato Kalinge Idrine; Nimusiima Godwin; Patrick Kitheka Muasya; Amina Abubakar Abdi; Kabera Radiana Makuza; John Martin Tumwebaza; Bayapa Reddy Narapureddy; Narayana Goruntla; et al. (Cancer Management and Research, 2026)
Background: Cancer is a major global health concern, causing significant morbidity and mortality, with particularly a high burden observed in low- and middle-income countries (LMICs). While chemotherapy remains a cornerstone of cancer treatment, it often causes adverse effects, particularly hepatotoxicity. Chemotherapy-induced hepatotoxicity (CIH) can severely compromise treatment effectiveness, often leading to necessary dose reductions or discontinuation, thereby increasing patient morbidity and mortality. Despite its clinical significance, there is currently limited data available on the incidence, severity, and risk factors of chemotherapy induced hepatotoxicity specifically within Uganda or LMIC. Objective: This study aimed to determine the incidence, severity, and risk factors with chemotherapy-induced hepatotoxicity among adult patients with cancer at the cancer unit of Mbarara Regional Referral Hospital (MRRH). Methods: A cross-sectional study was conducted among adult cancer patients receiving chemotherapy at MRRH. Data was collected through patient interviews, chart reviews, and laboratory assessments, including liver enzyme measurements. Statistical analysis was performed using STATA version 17 software. Results: Out of 216 adult patients with cancer. A total of 63 (29.2%) developed chemotherapy-induced hepatotoxicity. Most cases were of grade 1 (n = 51, 81%) followed by grade 2 (n = 8, 12.7%), then grade 3 (n = 4, 6.3%). Risk factors of chemotherapy-induced hepatotoxicity included; living with HIV (adjusted odds ratio (AOR) = 2.5, 95% CI: 1.1–5.6, p-value = 0.033) and diabetes mellitus (AOR = 20.2, 95% CI: 1.7–228.5, p-value = 0.015). Conclusion: Chemotherapy-induced hepatotoxicity affects about one in three cancer patients at MRRH, with HIV and diabetes significantly increasing risk. Routine liver function monitoring and individualized protocols, including prophylactic hepatoprotectants for high- risk patients, are essential to prevent severe hepatotoxicity and improve cancer treatment outcomes.
Keywords: incidence; risk factors; chemotherapy; hepatotoxicity; cancer; Mbarara